2022
DOI: 10.1037/tep0000372
|View full text |Cite
|
Sign up to set email alerts
|

Growth during a global pandemic: A polyethnography among doctoral counselling psychology students.

Abstract: The purpose of this paper is to distill knowledge gained from the impact of COVID-19 on psychology clinical training and education at the graduate level. We explore our experiences as counselling psychology doctoral students who were completing practica when the pandemic occurred, and mental health services were adapting to rapidly changing circumstances. We employed a polyethnographic qualitative research design, informed by a developmental lens, to identify ourselves as the site of research and participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Students reflected concerns over ineffective learning environments due to a sudden transfer to virtual learning, where they were unable to retain information and connect with people. [57][58][59][60][61] Potential technological breakdowns led to time wastage waiting for system recovery, while being constantly online gave rise to worries about work-life balance. 58,60 The lack of physical teaching and supervision also led to the fear of their inability to complete course requirements.…”
Section: Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students reflected concerns over ineffective learning environments due to a sudden transfer to virtual learning, where they were unable to retain information and connect with people. [57][58][59][60][61] Potential technological breakdowns led to time wastage waiting for system recovery, while being constantly online gave rise to worries about work-life balance. 58,60 The lack of physical teaching and supervision also led to the fear of their inability to complete course requirements.…”
Section: Studentsmentioning
confidence: 99%
“…58,60 The lack of physical teaching and supervision also led to the fear of their inability to complete course requirements. 58,60,61 Pregnant mothers Expectant mothers were fearful of catching COVID-19, especially near their delivery date, due to a lack of information about the birth and risk involved. [62][63][64][65][66][67] They also felt robbed of important life moments as they were unable to celebrate milestones, such as holding baby showers.…”
Section: Studentsmentioning
confidence: 99%
“…Importantly, their ability to learn effectively was informed by the dual‐space supervisory model utilised by the university. Well‐designed supervision promotes reflection (Pasyk et al, 2022) and, in this instance, it was crucial that students had these space(s) to deepen their understanding of their roles, responsibilities and acknowledge the accompanying emotionality resulting from their work.…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies, students stated that distance education saves time and is economical, provides easy access to information and also to materials and lessons (M. F. Genç Genç et al, 2020;Ünal et al, 2021). In addition, studies revealed that students' independent learning skills were developed in the distance education process (Öztürk, 2021;Pasyk et al, 2021). Kör et al (2013) also found that the use of interactive materials such as animation, video and simulation in distance education lessons had a positive effect on success.…”
Section: Discussionmentioning
confidence: 99%